Stability Analysis and Reliability Evaluation in Cataclastic Loose Rock Mass Blocks - Liguo Zhang; Dong Wang; Guanghe Li; Jiaxing Dong; Jianpeng Zhang (Advances in Civil Engineering)
Cataclastic rock masses with multiple failure modes and mechanisms are critical geological problems in the construction of rock slopes. Cataclastic rock masses are widely distributed in slopes of a hydropower project located on Lancang River, which is located in Tibet, China. In this study, the potentially unstable block of the slope is divided into key block and secondary key block based on the key block theory, and the system reliability evaluation theory is introduced. The method for quantitatively analyzing the rock mass stability of cataclastic slopes with sliding failure is established. Then, the spatial distribution of cataclastic rock masses and discontinuities in several rock slopes of a hydropower project are determined using traditional geological surveying and 3D laser scanning. At last, combining the BATE 2.0 software and the stereographic projection of the vector, the proposed method is applied to the study area. The results show that the main failure mode of the studied slope is wedge failure, and the system reliability is 1.69. With the increase in the instability probability of the key block, the increase in the instability probability of the system block is obvious, which reflects the controlling effect of the key block on the stability of the system block. The calculated system instability probability is slightly larger than the key block instability probability.